NECESIDAD DE EFECTIVIZAR EL DERECHO CONSTITUCIONAL DE PARTICIPACIÓN, ELIGIENDO UN REPRESENTANTE A LA ASAMBLEA NACIONAL POR LAS NACIONALIDADES DEL ECUADOR - JIMÉNEZ TORRES, JOHANNA ELIZABETH (2019)
This thesis entitled "The need to give effect to the constitutional right of participation by electing a representative to the National Assembly for the nationalities of Ecuador", is the product of the analysis and search for equity, equality and recognition of rights and principles enshrined in the Constitution of the Republic of Ecuador; concepts that generate importance for Ecuadorian indigenous nationalities, who for years have been disadvantaged by the effective recognition of their rights as primary duties of the State. This propensity has always been the voice of protest by the indigenous sectors in the country; since there is no representative in the National Assembly for the indigenous nationalities legally recognized in the country, they cannot participate directly in the creation of legal proposals and are only consulted on information through a commission, and therefore do not comply with Article 3, paragraph 3, of the Constitution of the Republic of Ecuador, which refers to one of the primary duties of the State, which is to strengthen national unity in diversity. The issuance of the 2008 Constitution, was intended to redress the discrimination and constant violations of which indigenous nationalities have been victims in the face of political and social norms prior to 2008. With that Constitution, however, the Ecuadorian State not only called itself a State of rights and justice, including the right to participation, but also recognized itself as a plurinational and intercultural State, but this has not been sufficient to ensure that the right of participation of indigenous nationalities is effectively fulfilled and in the manner in which it should be. In this way, it has not been 5 possible to provide credible solutions to the present problem that the indigenous nationalities of Ecuador have always experienced. The approach of this research work would be for the indigenous nationalities of Ecuador to elect a representative to the National Assembly, who would work on the proposal of laws in accordance with their culture and customs. The theoretical, legal and doctrinal collection, as well as the application of surveys and interviews, made it possible to carry out this research successfully and to conduct a broad discussion on the subject, resulting in clear and precise foundations on the need to make the right of participation effective, electing a representative to the National Assembly for the nationalities of Ecuador. For this reason, I express that, within the present topic analyzed, a real and feasible solution is proposed.